MASKED MEN DANCING AND THE LORDSHIP OVER LAND: a review essay - MAKISINYAU MAPIKO: MASKENTRADITIONEN IN BANTU-SPRACHIGEN AFRIKA, by Gerhard Kubik, Munchen: Trickster Verlag, 1993. - Nurse, G. T. (International Library of African Music, 1996)
pages: 96-102
Keywords: African Music